Education Financing and Infrastructure Delivery in Nigeria: Assessing the Role of Federal Matching Grants for Universal Basic Education Programme - Aule, Michael Mtomga; Okwoli, Ambrose Abalike; Jim-Suleiman, Saratu; Aule, Thomas Terna (Faculty of Natural and Applied Sciences Journal of Mathematical and Statistical Computing, 2025)
This study investigates the effect of the Federal Government Matching Grant (FGMG) on infrastructural development within Nigeria's Universal Basic Education (UBE) programme. Using panel data covering 30 states over 15 years (2009–2023), regression analysis revealed that FGMG exerts a positive and statistically significant impact on infrastructural development (p < 0.01). The findings confirm that consistent funding through the matching grant framework is a critical driver of improved educational facilities. However, the relatively modest explanatory power of the model suggests that additional factors such as governance quality, state-level implementation capacity, and community participation also play key roles in shaping infrastructural outcomes Aule et al., (2019). These results align with existing literature emphasising the importance of targeted education financing in reducing disparities and enhancing learning environments. The study recommends improved accountability, more substantial state commitment to counterpart funding, and increased federal allocation to education to maximise the impact of FGMG. It concludes that while the grant is an essential instrument for bridging infrastructural gaps, sustainable development in basic education requires complementary reforms, broader funding sources, and effective collaboration among stakeholders.